An immune activator encapsulating PD-L1 siRNA for augmented immune checkpoint blockade immunotherapy through Zn2+ overload triggered pyroptosis - Liming Gong; Yanhong Liu; Jing Feng; Congcong Xiao; Chenfei Liu; Bohan Chen; Liqing Chen; Mingji Jin; Youyan Guan; Zhonggao Gao; Wei Huang (Journal of Nanobiotechnology)
Abstract Breast cancer as a “cold” tumor presents an immunosuppressive microenvironment and inferior T-lymphocyte infiltration, leading to poor efficacy of immune checkpoint blockade (ICB) therapies. It is urgent to develop new effective combination treatment strategies. Pyroptosis is an inflammatory form of programmed cell death mediated by Caspase-1/GSDMD pathway, which can cause immunogenic cell death (ICD) and boost the immunogenicity of tumor. In this study, an immune activator (siRNAPD-L1@HA-ZIF-8) was proposed based on metal-organic framework (ZIF-8) nanosystem carrying Zn2+ and PD-L1 siRNA to improve anti-tumor immunotherapy through evoking pyroptosis combined with immune checkpoint blockade. We found that siRNAPD-L1@HA-ZIF-8 could disintegrate under low pH and release massive amounts of Zn2+, leading to elevated intracellular osmolarity and ROS, eventually resulting in pyroptosis. Zn2+ overload-triggered pyroptosis caused ICD effect and promoted the maturation of dendritic cells and infiltration of T-lymphocytes, which reprogramed the immunoecology of tumor from “cold” to “hot” state. Meanwhile, the co-delivered PD-L1 siRNA decreased the expression of PD-L1 protein on the tumor surface, relieving immune evasion and recovering the recognition and killing ability of cytotoxic T-lymphocytes, further boosting the immune response. This research not only confirmed the potential of ZIF-8 intrinsically as an immune activator that induces pyroptosis in combination with encapsulated PD-L1 siRNA-mediated ICB therapy for the first time, but also adequately revealed the immune responses mechanism by multiple techniques. This study will provide new strategies for pyroptosis-mediated treatments for augmented anti-tumor immunotherapy and greatly inspire the further development of immune activators based on Zn2+ overload-triggered pyroptotic pathway. Graphical abstract